Psycho-physiologic emergentism; four minds in a body - David L. Rowland; Ion G. Motofei (Journal of Mind and Medical Sciences, 2017)
The mind-body problem represents one of the most debated topics in the neurosciences. From a psychological standpoint, abstract/non-material data are an intrinsic part of the mind, intervening to a large extent in reasoning and decision making processes. Imaging studies also show a strong correlation between higher cognitive functions (such as working memory) and specific cerebral brain regions (a fronto-parietal network of interacting left and right brain areas). In contrast, the physical/material brain would be unable to interact with abstract-immaterial data, such that the psychological processing of abstract data (processes such as thinking, reasoning, and judgment) is attributed to the mind, with the mind representing a distinct entity interposed between the brain and abstract-immaterial data. Recent data suggest that the mind-body problem may simply be an artifact of human experience/ understanding, as the brain actually represents actually an intrinsic part of the mind. Even if the physical brain is not able to interact with abstract mental data, the brain still could process abstract data through a dynamic association between the abstract data and cerebral stimuli/ impulses. This form of processing without interaction defines the mind as a complex neurobiological structure, with the unconscious part of the mind processing abstract-immaterial data in a conscious/ mental format. In this overview, important concepts of psycho-physiologic emergentism, including internal mental reality, internal mental existence, internal mental interaction, and structural and informational dichotomies of the brain, are iterated. Such concepts/properties represent a neuro-informational support system capable of generating four distinct minds within the single brain. Future studies should further develop the dynamic and immaterial-material nature of the mind, as a possible premise for a scientific definition and understanding of mental events like affectivity, emotions, soul, etc.